1995
DOI: 10.1111/j.1476-5381.1995.tb16392.x
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent transport of procainamide in cultured renal epithelial monolayers of OK cells: consistent with nonionic diffusion

Abstract: 1 Previous studies suggest that procainamide is a substrate for organic cation/proton antiport. In order to study the coupling between procainamide flux and proton flux in greater detail we investigated the effects of extracellular procainamide addition upon intracellular pH in cultured monolayers of renal 5 Procainamide efflux from procainamide-loaded cell monolayers resulted in a significant acidification of intracellular pH. As with procainamide uptake, this result could be ascribed to the movement of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Furthermore from these experiments we can conclude that the permeability of the apical membrane to the unionised form of cimetidine must be small since at pH 7.4 and at pH 8.4, where almost all the cimetidine is in the unionised form (80% at pH 7.4, 97.5% at pH 8.4) we see no effect upon intracellular pH. This contrasts with the marked effect upon intracellular pH found with other weak bases such as procainamide where permeation of the unionised form of weak base across the apical membrane followed by a reduction in intracellular proton concentration as the weak a 6.6 -6.8 _-I.. base becomes protonated results in an intracellular alkalinisation (Dudley & Brown, 1995).…”
Section: Effects Of Cimetidine Upon Intracellular Phcontrasting
confidence: 72%
See 1 more Smart Citation
“…Furthermore from these experiments we can conclude that the permeability of the apical membrane to the unionised form of cimetidine must be small since at pH 7.4 and at pH 8.4, where almost all the cimetidine is in the unionised form (80% at pH 7.4, 97.5% at pH 8.4) we see no effect upon intracellular pH. This contrasts with the marked effect upon intracellular pH found with other weak bases such as procainamide where permeation of the unionised form of weak base across the apical membrane followed by a reduction in intracellular proton concentration as the weak a 6.6 -6.8 _-I.. base becomes protonated results in an intracellular alkalinisation (Dudley & Brown, 1995).…”
Section: Effects Of Cimetidine Upon Intracellular Phcontrasting
confidence: 72%
“…To do this, we have measured both transepithelial fluxes and initial rates of [3H]-cimetidine uptake across the apical and basolateral membranes of cultured LLC-PK, cells grown on permeable filter supports. In addition we have investigated the coupling of cimetidine transport to proton flux using the pH-sensitive fluorescent probe 2',7' -bis(2 -carboxyethyl) -5(6) -carboxyfluorescein (BCECF) (Dudley & Brown, 1995). The results suggest that cimetidine secretion across the apical membrane of LLC-PKI cells is mediated primarily by P-glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrated the potential of measurement of intracellular pH as a tool to characterize the relative contribution of charged and uncharged forms of a weak base to its overall transport ( Dudley & Brown, 1995 ; 1996 ). In this study, we set out to characterize the handling of the weak base metoprolol and related β‐adrenoceptor antagonists at the apical and basolateral membranes of epithelial monolayers of cultured renal LLC‐PK 1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pH (pH i ) was measured as previously described ( Thwaites et al ., 1993 ; Dudley & Brown, 1995 ). Briefly, cell monolayers grown on 12 mm diameter filter supports were loaded by incubation with BCECF‐AM (5 μ M ) in both the apical and basolateral chambers for 40 min at 37°C in culture media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation